2002
DOI: 10.1081/erc-120015059
|View full text |Cite
|
Sign up to set email alerts
|

Purine Metabolism in Leukocytes and Erythrocytes in Graves' or Hashimoto's Disease

Abstract: (1) ADA activity in leukocytes, obtained from patients with Hashimoto's disease, was significantly higher than in control leukocytes, as well as in leukocytes from patients with Graves' disease; (2) dCK activities in leukocytes from patients with both Graves' and Hashimoto's diseases were approximately four and five times higher, respectively, than in leukocytes of control subjects; (3) a positive correlation was observed between dCK activity in leukocytes and serum Tg Ab concentration in patients with Graves'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…As regards AITD, an increased ADA [Nishikawa et al, 1995; Covas et al, 1996; Karbownik et al, 2002] and dCK [Karbownik et al, 2002] activities were found in different blood fractions in patients suffering from Hashimoto's or Graves' disease. The increased expression of RNA for salvage enzymes in AITD speaks in favor of the assumption that in patients suffering from autoimmunological thyroid diseases the modification of these enzymes occurs at transcription level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards AITD, an increased ADA [Nishikawa et al, 1995; Covas et al, 1996; Karbownik et al, 2002] and dCK [Karbownik et al, 2002] activities were found in different blood fractions in patients suffering from Hashimoto's or Graves' disease. The increased expression of RNA for salvage enzymes in AITD speaks in favor of the assumption that in patients suffering from autoimmunological thyroid diseases the modification of these enzymes occurs at transcription level.…”
Section: Discussionmentioning
confidence: 99%
“…Increased activities of some enzymes, involved in nucleoside salvage metabolism, have been observed in blood fractions in patients suffering from different autoimmune disease [Hoshino et al, 1994; Hitoglou et al, 2001; Köse et al, 2001], autoimmunological thyroid disorders (AITD) included [Covas et al, 1996; Karbownik et al, 2002].…”
mentioning
confidence: 99%
“…Therefore, it is thought that ADA is an indicator of cellular immunity. Yet, there are a limited number of studies on ADA activity in hyperthyroid patients [2,29,[30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…ADA activity increased significantly compared to controls [29]. Reported that in homegenats of heart tissue of rats with experimental hyperthyroidism, ADA activity decreased by 15% in comparison to controls.…”
Section: Karbownik Et Al Established That In Patients With Graves Anmentioning
confidence: 99%
“…However, after 72 hours, activity of adenosine deaminase increased to match initial value. The activity of AMP-deaminase in the lymphocytes of the study group increased 2.4 times in comparison with the control 24 hours after the exposure and later maintained high values [12][13][14][15][16][17][18][19][20].…”
Section: Control Groupmentioning
confidence: 99%